Enhanced Dynamic Behaviour of Grid Connected Wind Farms in Load Participation and Frequency Regulation - Okedu, Kenneth E.; Barghash, Hind F. A. (Frontiers in Energy Research, 2021)
The control of grid frequency in power systems due to the penetration of wind turbines is vital to maintaining the stability of power grids, based on recent grid requirements. In this paper, the dynamic behaviour of a wind farm connected to an existing grid is presented. The existing grid is made up of steam turbines, while the wind farm is based on squirrel cage induction generators. An energy capacitor system is used to stabilize the wind farm during periods of wind speed change. Loads with various capacities were connected to the grid to test the robustness of the controllers of the energy capacitor system employed. Furthermore, the effect of varying the time constant of the in-built DC-DC chopper of the energy capacitor system was investigated, considering load participation in the grid. One of the targets of this paper is the stabilization of the grid frequency of the network, despite the load capacity and the nature of the wind speed in the wind farm. The system performance was evaluated using Power System Computer Design and Electromagnetic Transient Including DC (PSCAD/EMTDC). The same conditions of operation were used to investigate the various scenarios considered in this study, to ensure an effective comparison. The natural wind speed employed was the same for all the considered scenarios. The presented results show that small load capacity with a high value low pass filter time constant, provided better response for the grid frequency and the entire variables of the power network.